High-throughput multi-resolution three dimensional laser printing. (20th November 2018) - Tan, Yuanxin; Chu, Wei; Wang, Peng; Li, Wenbo; Qi, Jia; Xu, Jian; Wang, Zhanshan; Cheng, Ya
Abstract: Throughput and resolution are both of critical importance for modern manufacturing, however, they are usually contradictionary to each other. Here, the high-throughput multi-resolution three dimensional (3D) printing is demonstrated by incorporating a simultaneous spatiotemporal focusing (SSTF) scheme in two-photon polymerization. Remarkably, the SSTF can ensure generation of a spherical focal spot of which the size depends linearly on the laser power. Thus, the resolution can be continuously adjusted from sub-10 to ∼40 μ m by only increasing the laser power. A multi-resolution 3D structure is fabricated using this technique, for which the regions of coarse and fine feature sizes are produced at high and low resolutions, respectively.